Effects of amylose and amylopectin molecular structures on rheological, thermal and textural properties of soft cake batters. (December 2022) - Yang, Xiaoyan; Pan, Yujun; Li, Songnan; Li, Cheng; Li, Enpeng
Abstract: The rheological, thermal and textural properties of batter are critical for the eating and processing quality of soft cake products. Wheat starch molecular structures play an important role on these properties. However, the underlying mechanisms are not well understood. In this study, fluorophore-assisted carbohydrate electrophoresis and size-exclusion chromatography were used to measure amylopectin and amylose chain-length distribution. The obtained data were fitted with two different biosynthesis-based models, resulting in few biologically-meaningful parameters. For cake batter, the rheological, thermal and textural properties were measured by rheometer, differential scanning calorimetry and texture analyser. The length of amylose intermediate to long chains and amylopectin long chains was significantly positively correlated with the viscoelasticity of cake batter. The length of long amylose chains showed a negative correlation with the frequency value of crossover point between G′ and G″ curves. Moreover, different combinations of long amylopectin and intermediate-long amylose chains contributed to the formation of multi-endothermic gelatinization peaks. From flour-water system to flour-lipid-protein system, the main factors determining rheological and thermal properties changed from short amylopectin to long amylopectin and intermediate-long amylose chains. This study provides the first associations between starch molecular fine structure and functional properties of cake batter, which could help food industry breed and select suitable wheat varieties for improved batter quality. Graphical abstract: Image 1 Highlights: The functional properties of flour-lipid cake batter were investigated in this study. Long AP & medium and long AM chains are positively correlated with viscoelasticity. Decrease of long AM chain length increases crossover point x value of rheology curves. Cake batter shows two endothermic peaks in gelatinization curves. Chain length distribution of AM is the determining factor for flour-lipid batter.